Proposed framework for governance of municipal institutions to restrain of fraud: بحث تطبيقي في المؤسسات البلدية لمحافظة بابل (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The past decades have witnessed a development in the concept of corporate governance and the transformation of a concept that is limited to large companies listed in capital markets in major economies to an issue that concerns all business activities in the public and private sectors in both large and small countries. The aim of this research is to propose a guide to the mechanisms and rules of governance in the municipal institutions that contributes to the activation of the internal control system to reduce the fraud and manipulation of this activity. Institutions. The research was based on the hypothesis that the implementation of the principles and rules of governance in municipal institutions lead to the contribution of the activation of the internal control system. The researchers reached a number of conclusions. There is a clear weakness in the internal control systems of municipal institutions, with penetration by management and staff. Notably the strengthening of internal control systems to reduce fraud and large manipulation of municipal institutions and adopt the proposed framework for the governance of municipal institutions, which helps in achieving the goals and the development of municipal services providedextent of its contribution to the preservation of the environment from pollution, to reduce the spread of diseases and control them, and the need to adopt health and sustainable development indicators to measure progress, in the provision of health services and stand on the obstacles to achieving development and get closer to achieving development goals when developing plans and strategies and financial resources.